HUBUNGAN TINGKAT PENGETAHUAN TENTANG VAKSINASI COVID-19 TERHADAP SIKAP MASYARAKAT DI DUSUN KERANDEGAN-KEDUNGMLATI - Vendi Eko Kurniawan; Yusiana Vidhiaastutik; Priya Suma (Library Unit of the College of Health Science Husada Jombang, 2023)
Introduction: The Indonesian people have been afflicted by the Covid-19 virus outbreak for almost a year. The Covid-19 vaccine is one of the authorities's projects to prevent the Covid-19 virus from spreading. Objective: The purpose of this study was to see if there may be a link between Covid-19 vaccine understanding and public opinion. Methods: This have a look at used a pass-sectional correlational analytic layout. The study's population was 300 people, and the sample size was 45 people utilizing a basic random sampling procedure. The level of public understanding regarding Covid-19 immunization is the independent variable, while the community's attitude is the dependent variable. A questionnaire turned into applied as the research device, and the statistical Spearman Rank take a look at changed into used to research the outcomes. Results: According to the findings of this survey, the majority of respondents with good knowledge, 26 respondents (57.8%), had a positive attitude, whereas a tiny minority of respondents with less information, 3 respondents (6.7%), had a negative attitude. The statistical test yielded a p value of 0.001 and a p value of 0.0010.05, indicating that H1 was accepted, indicating that there was a link between Covid-19 vaccine knowledge and public opinions. Conclusion: It is hoped that health providers would be able to provide counseling about Covid-19 vaccination in order to raise public awareness and help people understand the benefits, dangers, and adverse effects of the vaccine.